Congenital coronary artery anomalies: a bridge from embryology to anatomy and pathophysiology--a position statement of the development, anatomy, and pathology ESC Working Group - Pérez-Pomares, José María; de la Pompa, José Luis; Franco, Diego; Henderson, Deborah; Ho, Siew Yen; Houyel, Lucile; Kelly, Robert G; Sedmera, David; Sheppard, Mary; Sperling, Silke; Thiene, Gaetano; van den Hoff, Maurice; et al. (Cardiovascular research, 2016)
Congenital coronary artery anomalies are of major significance in clinical cardiology and cardiac surgery due to their association with myocardial ischaemia and sudden death. Such anomalies are detectable by imaging modalities and, according to various definitions, their prevalence ranges from 0.21 to 5.79%. This consensus document from the Development, Anatomy and Pathology Working Group of the European Society of Cardiology aims to provide: (i) a definition of normality that refers to essential anatomical and embryological features of coronary vessels, based on the integrated analysis of studies of normal and abnormal coronary embryogenesis and pathophysiology; (ii) an animal model-based systematic survey of the molecular and cellular mechanisms that regulate coronary blood vessel development; (iii) an organization of the wide spectrum of coronary artery anomalies, according to a comprehensive anatomical and embryological classification scheme; (iv) current knowledge of the pathophysiological mechanisms underlying symptoms and signs of coronary artery anomalies, with diagnostic and therapeutic implications. This document identifies the mosaic-like embryonic development of the coronary vascular system, as coronary cell types differentiate from multiple cell sources through an intricate network of molecular signals and haemodynamic cues, as the necessary framework for understanding the complex spectrum of coronary artery anomalies observed in human patients.
Keywords: kardiologie; Coronary Vessel Anomalies; Coronary Vessels; Coronary Artery Disease; Pathology; anomálie koronárních cév; srdce; Cardiology; Coronary arteries; Myocardial Ischemia; nemoci koronárních tepen; Embryology; Animals; lidé; Humans; zvířata; Anatomy; koronární cévy; ischemická choroba srdeční; Heart; Congenital heart disease